Contribution of informal shallow groundwater irrigation to livelihoods security and poverty reduction in the White Volta Basin (WVB): Current status and future sustainability - Barry, Boubacar; Forkuor, Gerald (CGIAR Challenge Program on Water and Food, 2010)
Shallow groundwater irrigation (SGI) using hand-dug shallow wells and dugouts is expanding, in the WVB, and is becoming attractive to farmers throughout. SGI is farmer-driven and has developed without any government or donor involvement. The production of vegetables and cash crops during the dry season utilizing SGI has provided farmers with a supplemental source of income and an alternative to seasonal urban migration. Although SGI has been increasing substantially, the extent of this practice is not documented.This project has help assess, the impacts of intensive SGI on sub-basin hydrology, net groundwater recharge farmers' livelihoods and on rural poverty reduction in the Atankuidi catchment a tributary of the WVB with the highest per capita groundwater use.